A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae) - Hrúzová, Kamila; Mašán, Peter; Fenďa, Peter (Zootaxa, 2017)
The originally monotypic genus Anadenosternum Athias-Henriot, 1980 is revised and redefined. A new species Anadenosternum okalii sp. nov. is described and illustrated based on adult specimens collected in park litter in Bergamo, Italy. The type species of the genus, Anadenosternum azaleense (Daele, 1975), is redescribed and illustrated from adults and deutonymphs collected in soil detritus of greenhouses in the Botanic Garden in Bratislava, Slovakia. Anadenosternum pediculosum Karg & Glockemann, 1995 is considered to be a junior synonym of A. azaleense. The genus Anadenosternum is recorded from Italy and Slovakia for the first time. An identification key to known species of the genus is provided.